Metastatic Colon Cancer in an 18-Year-Old without Predisposing Factors. (27th March 2016) - Mirchandani, Divya; Kulpa, Jolanta; Khawar, Nayaab; Kochin, Israel; Narula, Pramod; Sundaram, Revathy
Abstract : While colorectal carcinoma is a common gastrointestinal cancer in adults, it is rare in pediatrics with an incidence of 1 : 1, 000, 000 and represents a fraction of neoplasms encountered in children. Malignant neoplasms represent a major cause of mortality in the pediatric age group. While presenting with weight loss, iron deficiency, rectal bleeding, abdominal pain, and change in bowel habits, or symptoms similar to acute appendicitis, the working diagnosis may be considered to be anorexia. This case illustrates the importance of considering colon cancer among other disease entities as a cause of unintentional weight loss in adolescents. While this is a rare occurrence in the pediatric population, significant unintentional weight loss with altered bowel habits should prompt a search for underlying malignancy—even in the absence of a positive family history or predisposing cancer syndromes.